Analisis Kesulitan Belajar Bahasa Inggris Siswa Di Kelas XI TKJ SMK N 1 BANGLI - I Gede Sade Dadi (BADAN PENERBIT STIEPARI PRESS, 2024)
This study investigates the challenges faced by vocational high school students in learning English, focusing on Class XI Computer and Network Engineering in SMK Negeri 1 Bangli. Drawing on the insights of education and linguistic experts, the research identifies key factors such as non-native English status, motivation issues, and limited vocabulary mastery that contribute to the difficulties encountered by students. Findings from interviews, questionnaires, observations, and academic performance analysis highlight the need for tailored teaching approaches, relevant materials, and motivational strategies to enhance English language learning. The study emphasizes the importance of active student engagement and ongoing evaluation of teaching methods, aiming to create a supportive learning environment and improve overall learning outcomes in English for vocational high school students.